OPTIMALISASI PERAN PEMERINTAH DESA PADA PELINDUNGAN TENAGA KERJA MIGRAN INDONESIA GUNA MENJAMIN KESEJAHTERAAN SOSIAL DAN EKONOMI - Aliardo, Mohammad (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Indonesian migrant workers or often called Indonesian Migrant Workers (PMI) are one of Indonesia's foreign exchange earners. PMI also helps reduce the number of unemployed in Indonesia. However, the existence of PMI is not free from various problems, especially migrant workers who are sent abroad illegally. In addition, PMI who are legally sent abroad are also not free from various existing problems. For that, based on the mandate of Law Number 18 of 2017, the village government has the duty and responsibility to protect Indonesian Migrant Workers.